Assessing the reaction to and efficacy of the Screener drug discovery and development board game as a pedagogical tool in postgraduate courses - Noël, F.; Xexéo, G.; Martins, M. A.; Silva, E. J.R. [UNESP]; Pupo, A. S. [UNESP]; Magalhães, P. J.C.; Lima-Júnior, R. C.P.; Gadelha, K. K.L.; Lima-Silva, K.; Raimundo, J. M.; Ghedini, P. C.; Crespo-Lopez, M. E.; et al. (FapUNIFESP (SciELO), 2024)
Screener, a board game supplemented with online resources, was introduced and distributed by the Brazilian Society of Pharmacology and Experimental Therapeutics to postgraduate programs as an instructional tool for the process of drug discovery and development (DDD). In this study, we provided a comprehensive analysis of five critical aspects for evaluating the quality of educational games, namely: 1) description of the intervention; 2) underlying pedagogical theory; 3) identification of local educational gaps; 4) impact on diverse stakeholders; and 5) elucidation of iterative quality enhancement processes. We also present qualitative and quantitative assessments of the effectiveness of this game in 11 postgraduate courses. We employed the MEEGA+ online survey, comprising thirty-three close-ended unipolar items with 5-point Likert-type response scales, to assess student perceptions of the quality and utility of Screener. Based on 115 responses, the results indicated a highly positive outlook among students. In addition, we performed a preliminary evaluation of learning outcomes in two courses involving 28 students. Pre-and post-quizzes were applied, each consisting of 20 True/False questions directly aligned with the game’s content. The analysis revealed significant improvement in students’ performance following engagement with the game, with scores rising from 8.4 to 13.3 (P<0.0001, paired t-test) and 9.7 to 12.7 (P<0.0001, paired t-test). These findings underscore the utility of Screener as an enjoyable and effective tool for facilitating a positive learning experience in the DDD process. Notably, the game can also reduce the educational disparities across different regions of our continental country.
Keywords: Active learning; Drug discovery; Educational game; Game-based learning; Postgraduate course; Survey